Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1371/journal.pone.0224515
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety among pregnant women living with HIV in Kilimanjaro region, Tanzania

Abstract: IntroductionMental health disorders in pregnant women living with HIV are associated with poor maternal and child outcomes, and undermine the global goals of prevention of mother-to-child transmission of HIV (PMTCT). This study aimed to determine prevalence of depression and anxiety and identify factors associated with these common mental health disorders among HIV-infeced pregnant women in Tanzania.MethodsWe enrolled 200 pregnant women living with HIV from antenatal care clinics in the Kilimanjaro region. Wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 48 publications
(54 reference statements)
6
64
2
Order By: Relevance
“…According to Dell'Osso and Pini [ 26 ], the possible clarifications for these comorbid mental illnesses might be that both disorders are likely to share the same phenomena or common symptoms or vulnerabilities. Upon close examination, the findings revealed that the point prevalence of these comorbid illnesses is marginally higher than the institutional-based cross-sectional study conducted on pregnant women in Tanzania (18.1%) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Dell'Osso and Pini [ 26 ], the possible clarifications for these comorbid mental illnesses might be that both disorders are likely to share the same phenomena or common symptoms or vulnerabilities. Upon close examination, the findings revealed that the point prevalence of these comorbid illnesses is marginally higher than the institutional-based cross-sectional study conducted on pregnant women in Tanzania (18.1%) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The scores of anxiety and insomnia symptoms ( r = 0.719), along with scores of depression and insomnia symptoms ( r = 0.698) were positively correlated in these samples. Previous studies suggested that environmental stressors or physiological disease might cause the comorbidity of anxiety, depression, or insomnia, which could provide a great challenge in the diagnosis and intervention [ 32 , 33 ]. The comorbidity of anxiety and depression could make psychological distress worse and reduce treatment response, which should be considered [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The data collection instrument was organized after reviewing previous literature [ 5 , 12 , 17 , 24 , 40 ]. The tool comprises socio-demographic information (age, marital status, religion, residence, educational status, occupation and husband education and occupation), socioeconomic status (assessed using locally available assets), obstetric characteristics (gravidity, parity, age at marriage, pregnancy status, ANC visit, gestational age, pregnancy danger signs), psychological problems and psychosocial relationships (social support, interpersonal relationship and experience of life-threatening events), medical illness (hypertension, diabetes, asthma, cardiac and renal disease), household food security status, substance abuse, anxiety and depression.…”
Section: Methodsmentioning
confidence: 99%